Hippocampal network oscillations in APP/APLP2-deficient mice - Zhang, Xiaomin; Weyer, Sascha W.; Both, Martin; Müller, Ulrike C.; Draguhn, Andreas (PLOS ONE, 2013)
The physiological function of amyloid precursor protein (APP) and its two homologues APP-like protein 1 (APLP1) and 2 (APLP2) is largely unknown. Previous work suggests that lack of APP or APLP2 impairs synaptic plasticity and spatial learning. There is, however, almost no data on the role of APP or APLP at the network level which forms a critical interface between cellular functions and behavior. We have therefore investigated memory-related synaptic and network functions in hippocampal slices from three lines of transgenic mice: APPsα-KI (mice expressing extracellular fragment of APP, corresponding to the secreted APPsα ectodomain), APLP2-KO, and combined APPsα-KI/APLP2-KO (APPsα-DM for “double mutants”). We analyzed two prominent patterns of network activity, gamma oscillations and sharp-wave ripple complexes (SPW-R). Both patterns were generally preserved in all strains. We find, however, a significantly reduced frequency of gamma oscillations in CA3 of APLP2-KO mice in comparison to APPsα-KI and WT mice. Network activity, basic synaptic transmission and short-term plasticity were unaltered in the combined mutants (APPsα-DM) which showed, however, reduced long-term potentiation (LTP). Together, our data indicate that APLP2 and the intracellular domain of APP are not essential for coherent activity patterns in the hippocampus, but have subtle effects on synaptic plasticity and fine-tuning of network oscillations.
Gesehen am 18.12.2024